Functional Outcome Of Percutaneous K-Wires System In Elder Patients With Proximal Humeral Fractures - Ali, Waqas; Akhtar, Rahman Rasool; Ahmed, Riaz; Siddiq, Muhammad Zahid; Ahmad, Nisar; Kashmiri, Muhammad Nadeem (Journal of Rawalpindi Medical College, 2024)
Objective: To evaluate the functional outcome of the percutaneous K-wires system in elder patients with proximal humeral fractures. Method: This one-year observational prospective study was conducted on 68 patients aged 50 to 70 years with proximal humeral fractures, treated at the Orthopaedic Department of Benazir Bhutto Hospital, Rawalpindi. Participants with NEER two-, three-, or four-part fractures, capable of participating in follow-up assessments, were included. Percutaneous K-wire fixation was performed, and standardized postoperative care was administered. Chi-Square test and Pearson’s Coefficient Correlation were used for the assessment of association. Results: The mean age of the patients was 59.65 ± 6.47 years. Gender distribution revealed 29 (42.6%) male and 39 (57.4%) female patients. Assessing functional outcomes, 20.60% of patients exhibited an excellent outcome, 64.70% showed a good outcome, 11.80% displayed a fair outcome, and 2.90% experienced a poor outcome. Conclusion: The use of K-wire fixation for humerus fractures produces exceedingly favourable outcomes in the post-operative context in elderly patients.